How to make Lesson Study work in America and worldwide: A Japanese perspective on the onto-cultural basis of (teacher) education. (December 2017) - Rappleye, Jeremy; Komatsu, Hikaru
Lesson Study is a Japanese approach to teacher development borrowed by American researchers in the late 1990s seeking to break from top-down, "best practice" approaches. Two decades later, Lesson Study has gained a strong foothold in American policy circles. Seeking to contribute to the growing research base, this article looks deeper into the cultural obstacles obstructing effective practice in the American context. It suggests that the divergent onto-cultural basis of the Japanese context may be one major factor that helps make Lesson Study successful in Japan but challenging in other national contexts worldwide, perhaps most of all in the United States. The account is based on a meta-analysis of existing research on Lesson Study (1999–2015), combined with a reconceptualization of a rich ethnographic literature on compulsory schooling in Japan. This account frames the American borrowing of Japanese teacher developed practice in terms of educational borrowing and lending, suggesting that scholars need to return to the puzzle of culture, engage philosophically, and be open to ontological alterity.